The Meaning of Idiom in My Dagestan Book, Translated by Aziz Gardi - Ali Mustafa Najmaddin; Farman Muhsin Abdulle (Zanco Journal of Human Sciences, 2024)
This research entitled (The Meaning of Idiom in My Dagestan Book, translated by Aziz Gardi), is a scientific project, based on the method of analytical criticism, in which the theory of idiom is discussed Idioms, culture, use and benefits of idioms are discussed, which are confirmed by examples of idioms in the book, and in practical topics, the essence of idioms in My Dagestan is discussed in several topics, all these topics with vivid examples in the first and second books My Dagestan has been enriched, read and analyzed. This research describes a cultural process in which idioms give commonality and vivid color to Kurds in all parts of Kurdistan. Through idioms we reach the fact that is a source of pride and glory, which is to keep alive the customs and traditions of society.